Management of biofuel sorghums in Kansas - Dooley, Scott J. (Kansas State University, 2010)
Current demand for ethanol production is stressing feedstock production. Previous research has shown sweet sorghum and photoperiod sensitive sorghum [Sorghum bicolor (L.) Moench] as viable feedstocks which may supplement or replace current feedstocks. Studies were conducted at two dryland locations in north central and northeast Kansas in 2008 and 2009 to determine the effects of cultivar, nitrogen fertilizer rate, plant density, and harvest date on sweet sorghum juice and biomass yields. The cultivar study indicated the cultivar ‘M81E’ generally had the greatest yield. Other cultivars were not well suited for this region. No significant results were found in the nitrogen rate trial, indicating sweet sorghum may be insensitive to nitrogen fertilizer applications. The plant density trial results indicated that sweet sorghum possess a great ability to compensate for plant spacing. No differences were found in juice yields across densities, and the only difference found in total dry biomass was at the highest plant density. Results from the harvest date study indicate that sweet sorghum harvest should be delayed until at least the grain soft dough stage and can be continued for at least 10 days after a killing freeze without a yield penalty. Delaying harvest allowed for an increase in total dry matter and fermentable carbohydrates without a decrease in juice yield. Two studies were conducted at two dryland locations in northcentral and northeast Kansas in 2008 and 2009 to determine the effects of plant density on photoperiod sensitive sorghum yields, with an additional study to determine the effects of winter weathering. Photoperiod sensitive sorghum was found to be similarly insensitive to plant density, with few differences found in total dry biomass yield. Yields were found to decrease significantly due to winter weathering. A final study was conducted to examine a variety of sorghums as biofuel feedstocks. Photoperiod sensitive sorghum yielded the greatest in 2008 while sweet sorghum yielded less. In 2009, sweet and photoperiod sensitive sorghum yielded less than the cultivar TAMUXH08001. Sweet sorghum yields are generally the greatest with ‘M81E’ and when harvested after soft dough. Yields of both sorghums are occasionally influenced by plant density.
Keywords: Sweet Sorghum; Photoperiod Sensitive Sorghum; Biofuel Feedstock; Agriculture, Agronomy (0285)